Економічні права та свободи людини в Україні: поняття, види, загальний огляд - Федоренко, В.; Fedorenko, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена розкриттю сутності та змісту основних економічних прав і свобод людини в Україні в реаліях сьогодення. Відзначається, що економічні права і свободи громадян, поряд з їх особистими правами, утвердились одними із перших ще в період буржуазно-демократичних революцій у Європі та воєн за незалежність у Америці в кін. XVIII-XIX ст. Здійснено характеристика основних економічних прав і свобод громадян, визначених Конституцією України, а саме: права приватної власності(ст. 41); права на підприємницьку діяльність, яка не заборонена законом(ст. 42); права на користування об’єктами права державної та комунальної власності (ст. 41) та власністю Українського народу(ст. 13). The article reveals the essence and importance of basic economic rights and freedoms in Ukraine in the realities of our time. It is noted that the economic rights and freedoms of people, together with their personal rights, firmly established themselves in the period of bourgeois-democratic revolutions in Europe and the wars of independence in the Americasat the end of XVIII-XIX centuries. Over the past 300 years the economic rights and freedoms gained basismechanisms for their implementation and protection, but have not lost their fundamental importance for the formation and functioning of the so-called «middle class», which is the social-economic basis in the majority economically developed countries in the world. The emphasis is laid on the characteristics of the fundamental rights, economic rights and freedoms ofthe citizens defined by the Constitution of Ukraine, namely: the right to private property (Art. 41); the right to entrepreneurial activity that is not prohibited by law (Art. 42); the right to use objects of the state or municipal property (Art. 41) and the common property of the Ukrainian people (Art. 13).
Economic Rights and Freedoms of a Person in Ukraine: Concept, Types, General Overview
Keywords: права та свободи людини; приватна власність; власність Українського народу; економіка; підприємництво; економічні права і свободи людини; human rights and freedoms; private property; the property of the Ukrainian people; economy; entrepreneurship; economic rights; human rights and freedoms